FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KENAIKAN BERAT BADAN PADA PENGGUNAAN KB SUNTIK 1 BULAN DAN 3 BULAN - Muayah, Muayah (Jurnal Ilmiah Bidan (JIB), 2022)
Background: Injectable contraceptives for one month or three months can cause side effects, one of which is weight gain. Weight gain is a problem for women. The purpose of the study was to determine the factors associated with weight gain on the use of 1-month and 3-month injectable contraception in the working area of the Puskesmas Kelurahan Pulau Panggang, Seribu Islands in 2021. Methods: Analytical research with case control design. The sample of this study was acceptors who used 1-month and 3-month injectable KB for 1 years starting from Mei 2020 totaling 106 consisting of 53 acceptors of 1-month injectable KB and 53 acceptors of 3-month injectable KB using purposive sampling technique. The research instrument used a questionnaire. Data is primary data analyzed using Spearman test. Result: Research on physical activity (p=0.000), stress (p=0.000) and nutritional intake (p=0.002), with an odd ratio value of physical activity of 7.901, the value of the Odds Ratio of stress was 5.638, the odd ratio value of nutritional intake was 3.789. The conclusion of this research is the weight gain of 3month injection family planning acceptors was more than that of 1 month family planning acceptors. Physical activity, stress and nutritional intake are among the factors associated with weight gain. Suggestions for injection family planning acceptors, it is expected that they will exercise regularly and be able to regulate their diet with a balanced nutritional menu so that the mother's weight is reduced and ideal so as to avoid the incidence of obesity.